Visualizing orthogonal RNAs simultaneously in live mammalian cells by fluorescence lifetime imaging microscopy (FLIM) - Nadia Sarfraz; Emilia Moscoso; Therese Oertel; Harrison J. Lee; Suman Ranjit; Esther Braselmann (2023)
Abstract Visualization of RNAs in live cells is critical to understand biology of RNA dynamics and function in the complex cellular environment. Detection of RNAs with a fluorescent marker frequently involves genetically fusing an RNA aptamer tag to the RNA of interest, which binds to small molecules that are added to live cells and have fluorescent properties. Engineering efforts aim to improve performance and add versatile features. Current efforts focus on adding multiplexing capabilities to tag and visualize multiple RNAs simultaneously in the same cell. Here, we present the fluorescence lifetime-based platform Riboglow-FLIM. Our system requires a smaller tag and has superior cell contrast when compared with intensity-based detection. Because our RNA tags are derived from a large bacterial riboswitch sequence family, the riboswitch variants add versatility for using multiple tags simultaneously. Indeed, we demonstrate visualization of two RNAs simultaneously with orthogonal lifetime-based tags.